2012
DOI: 10.1074/jbc.m111.312736
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived Neurotrophic Factor (BDNF) Induces Polarized Signaling of Small GTPase (Rac1) Protein at the Onset of Schwann Cell Myelination through Partitioning-defective 3 (Par3) Protein

Abstract: Background: Both p75 and Par3 become localized in a polarized manner in Schwann cells. Results: BDNF activates Rac1 at the axon-glial interface, regulated by Par3, thereby facilitating proper alignment between the axon and Schwann cells. Conclusion: Polarized localization of Rac1 activation is critical for myelination. Significance: Par3 is involved in Rac1 activation by BDNF-p75 at the axon-glial interface, thereby promoting myelination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
4
37
0
Order By: Relevance
“…Thus, our data suggest that p75NTR-dependent cell spreading is dependent on generation of the p75NTR ICD , which in turn drives NRAGE-and NEDD9-dependent activation of Rac1. Although generation of the p75NTR ICD , NRAGE signaling and Rac1 activation have all been proposed to play important roles downstream of p75NTR (Salehi et al, 2002, Harrington et al, 2002, Domeniconi et al, 2005, Kenchappa et al, 2006, Bertrand et al, 2008, Wang et al, 2008, Kenchappa et al, 2010, Ceni et al, 2010, Tep et al, 2012, Matusica et al, 2013, this is the first study that links these events in a single cascade.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, our data suggest that p75NTR-dependent cell spreading is dependent on generation of the p75NTR ICD , which in turn drives NRAGE-and NEDD9-dependent activation of Rac1. Although generation of the p75NTR ICD , NRAGE signaling and Rac1 activation have all been proposed to play important roles downstream of p75NTR (Salehi et al, 2002, Harrington et al, 2002, Domeniconi et al, 2005, Kenchappa et al, 2006, Bertrand et al, 2008, Wang et al, 2008, Kenchappa et al, 2010, Ceni et al, 2010, Tep et al, 2012, Matusica et al, 2013, this is the first study that links these events in a single cascade.…”
Section: Discussionmentioning
confidence: 97%
“…p75NTR can also mediate Rac1 regulation. In some settings, this links the activated receptor to the JNK signaling cascade and promotes apoptosis (Harrington et al, 2002), and in others, p75NTR collaborates with Par3 to localize Rac1 to the axon-glial interface and thereby promote myelination (Tep et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry-Brains were sectioned at 30 m in a sagittal or coronal plane using a cryostat and used for immunohistochemistry as described (4). For p-PAK staining, tissues were subjected to antigen retrieval at 50°C for 50 min in 10 mM Tris-HCl (pH 9.0).…”
Section: Methodsmentioning
confidence: 99%
“…Of the signaling pathways that p75 activates, we focused on a small GTPase, Rac1. We have previously reported that p75 activates Rac1 in neural cultures (3,4). In cultured dorsal root ganglion neurons, Rac1 mediated up-regulation of GIRK channels through increasing phosphatidylinositol 4,5-bisphosphate synthesis, which underlies the neuronal death mechanism activated by p75 cleavage (15).…”
Section: P75 Modulates Spontaneous Firing Properties Of Purkinjementioning
confidence: 97%
See 1 more Smart Citation